Peranan Hukum dalam Pengelolaan Sumber Daya Alam Kehutanan di Tinjau dari Undang-Undang Kehutanan - Darnia, Meriza Elpha; Binandar, Agustian; Hakiki, M. Haikal; Afifah, Lia; Azura, Fahima (Jurnal Ilmiah Wahana Pendidikan, 2024)
Areas set aside by the government for the purpose of permanent forestation are known as forest areas. In addition, the state decides who has jurisdiction over forest regions, which might be either forested or unforested. The forestry sector in Indonesia has decided, or will determine based on the requirements and interests of the Indonesian people, the use of all lands that are considered forest areas in land use planning. A normative juridical legal research approach was used in this investigation. Research in the field of normative law often makes use of secondary data, including primary, secondary, and tertiary legal sources, to investigate issues with the law and its guiding principles. Here, nevertheless, the author is interested in learning more about the function of legislation in NRM. Tree Service Forestry Law evaluated the case.